Mortality Among Patients With Chronic Hepatitis B Infection: The Chronic Hepatitis Cohort Study (CHeCS). (28th July 2018) - Bixler, Danae; Zhong, Yuna; Ly, Kathleen N; Moorman, Anne C; Spradling, Philip R; Teshale, Eyasu H; Rupp, Loralee B; Gordon, Stuart C; Boscarino, Joseph A; Schmidt, Mark A; Daida, Yihe G; Holmberg, Scott D; et al.
Abstract: Background: According to death certificates, approximately 1800 persons die from hepatitis B annually in the United States; however, this figure may underestimate true mortality from chronic hepatitis B (CHB). Methods: We analyzed data from CHB patients seen in the Chronic Hepatitis Cohort Study (CHeCS) between 1 January 2006 and 31 December 2013. We compared overall and cause-specific death rates and mean ages at death between CHeCS CHB decedents and U.S. decedents from the Multiple Cause of Death (MCOD) file. Results: Of 4389 CHB patients followed for a mean of 5.38 years, 492 (11%) CHB patients died after a mean follow-up of 3.00 years. Compared to survivors, decedents were older, more likely to be White (40.6%), African-American (27.1%), or male (74.2%); and more likely to have had cirrhosis (59.8%), diabetes (27.2%), alcohol abuse (17.7%), hepatocellular carcinoma (17.5%), or a liver transplant (5.7%); whereas survivors were more likely to be Asian (48.8%; all P < .001). CHB patients died at an average age of 59.8 years—14 years younger than the general U.S. population—and at higher rates for all causes (relative risk [RR] = 1.85, 95% confidence interval [CI], 1.851–1.857) and liver-related causes (RR = 15.91, 95% CI, 15.81–16.01). Only 19% of CHB decedents and 40% of those dying of liver disease had hepatitis B reported on their death certificates. Conclusions: Compared to the general population, CHB patients die at younger ages and higher rates from all causes and liver-related causes. Death certificates underrepresent the true mortality from CHB. Abstract : Half of decedents with chronic hepatitis B (CHB) died of liver-related causes, at an average age of 60 years. Despite this, only 40% of CHB decedents dying with liver disease had hepatitis B reported on the death certificate.